Heritability evaluation of fear emotional states among people of Ukraine - Філіпцова, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Genetic analysis of fears was performed on the Ukraine population sample for the first time. As a result of the research of Ukraine population sample correlation coefficients of fears emotional states were obtained (correlation coefficients ρ were in the range 0,18–0,77). In majority of cases correlation coefficients were higher in sibling pairs comparatively with «parent-offspring» pairs. For three fears (psychiatric disorders development, disease of relatives and suicide commitment) there is a positive assortative mating in the population (correlation coefficients ρ were in the range 0,35–0,43), that made essential to modify correlation coefficients between relatives for a genetic analysis purpose. Heritability coefficients of nine fears were in the range 26–48 %, among them the lowest heritability coefficient was related to a fear of suicide commitment and the highest one for a fear of aggressive behavior possibility to the relatives.